2010
DOI: 10.1007/s10238-010-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum prealbumin (transthyretin) predict good outcome in young patients with cerebral infarction

Abstract: Low serum protein and albumin are considered to significantly associate with malnutrition, impaired functional status, poor outcome, and mortality. We hypothesized that serum prealbumin (transthyretin, PA) was a reliable and robust survival marker in young cerebral infarction patients and attempted to test the foregoing hypothesis. We analyzed the relationship between serum PA and stroke severity as determined by the modified Rankin Scale at discharge in 585 young cerebral infarction patients. By multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…Transthyretin was independently associated with functional outcome at discharge and one-year mortality in stroke patients, after adjusting for potential confounders. As a matter of fact, one research group explored the similar field but this study has several concerns [15]. Participants were young (the mean age was 39 years) and have been enrolled only from Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Transthyretin was independently associated with functional outcome at discharge and one-year mortality in stroke patients, after adjusting for potential confounders. As a matter of fact, one research group explored the similar field but this study has several concerns [15]. Participants were young (the mean age was 39 years) and have been enrolled only from Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with heart failure, cancer, and cerebral infarction, prealbumin has been shown to be a good predictor of prognosis [6], [7], [8]. It has been reported that serum prealbumin also has predictive value for TBI [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with acute stroke, lower serum albumin concentration predicted mortality during hospitalization and the need for institutional care [12]. In young patients with ischemic stroke, serum prealbumin (transthyretin, PA) was also an independent predictor of clinical outcome [24]. …”
Section: Malnutrition As a Risk Factor For Adverse Outcomesmentioning
confidence: 99%